Factors That Affect The Income of PT. SIL: Cashiers Perspectives - Yulianti, Lastri; Sungkono, Sungkono (Integrasi Sains Media, 2023)
Retail companies market products by involving the sale of products by retailing to consumers through stores, minimarkets, supermarkets, and others. There have been many retail companies that have grown. One of them is PT SIL. The purpose of research at PT SIL is to determine the factors that affect the income of cashiers who sometimes experience income differences. The research method used is an implementation method. The results showed several obstacles to the cashier's income, namely the accuracy of the performance cashier's performance. Moreover, it can be concluded that the cashier plays an important role in the presence or absence of differences in income.